Hubungan Tingkat Kesadaran Pengguna terhadap Cybercrime dan Pengaplikasian Fitur Peringatan Phishing dan Malware Pada Google Browser - Fadhlirrahman Baso; Muhammad Rahmat Ramadan (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The high number of cybercrime cases shows the need for user awareness to avoid various crimes on the internet. This research aims to determine whether there is a relationship between the level of user awareness of cybercrime threats and the level of application of the phishing and malware warning features on the google browser. The researcher uses a quantitative approach. Data was obtained from questionnaires and analyzed using the Pearson coefficient correlation method. By using this method, a positive correlation coefficient value was found between the two variables. The positive correlation coefficient value indicates that there is a relationship between the two variables.